The Role of Employer Brand Reputation on Talent Acquisition and Retention in Fast-Food Small and Medium Enterprises in Maseru Urban - Mok’hena, Nthabiseng; Motsomotso, Maletlatso (Asian Journal of Management Analytics, 2025)
Employer branding has drawn attention from all over the world yet little is known about the role played by SME managers in implementing and assessing brand reputation.  This study examined the role of brand reputation on talent acquisition and retention in fast-food Small and Medium Enterprises in Maseru Urban.  A quantitative approach was used, where structured questionnaires were distributed to 36 managers and owners. The findings revealed that most managers inconsistently apply brand monitoring, employee-aligned culture, and internal brand communication. Results also showed a weak and statistically insignificant relationship between brand reputation practices and recruitment efficiency.  The current study highlights the importance of enhanced strategic training, continuous brand alignment, and the consistent use of brand messaging during recruitment processes.